(untitled) (Proceedings of the International Conference on Future of Women, 2018)
The present paper explores the relationship between gender and virtual space and studies how virtual space reproduces the gendered relations of power. Manjula Padmanabhan’s play Harvest (1998) locates the female body in different positions in the real and virtual spaces. Technology rather confirms the existing gendered meanings assigned to the human body as it is shaped by the particular social and cultural patterns. In the play, Ginni is a virtual figure who controls Om, Jaya and their family through a virtual device called the Contact Module. Gender swapping of virtual Ginni/Virgil suggests not a denial of gender but the assertion of it. The virtual space does not liberate individuals from gendered bodies but emphasizes the gender differences, objectifies the body and confirms the binary of man/woman by projecting them into animated double figures. Manjula Padmanabhan, in the play, presents a frightening vision of a futuristic, technologically advanced world with gender imbalance against the popular images of romantic, fancy, beautified and easy going virtual world. In the given context, the paper analyses the idea that a virtual body is a cultural entity and explains how the idea of human body becomes a technological construction. The research is a textual study and analytical and descriptive methods are applied to it.